2019
DOI: 10.1002/dvg.23290
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of position effect variegation at pericentric heterochromatin by Drosophila Keap1‐Nrf2 xenobiotic response factors

Abstract: Summary The Keap1‐Nrf2 signaling pathway plays a central role in the regulation of transcriptional responses to oxidative species and xenobiotic stimuli. The complete range of molecular mechanisms and biological functions of Keap1 and Nrf2 remain to be fully elucidated. To determine the potential roles of Keap1 and Nrf2 in chromatin architecture, we examined the effects of their Drosophila homologs (dKeap1 and CncC) on position effect variegation (PEV), which is a transcriptional reporter for heterochromatin f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Our previous studies found that knockout of dKeap1 reduced the level of heterochromatin marker histone H3K9me2, suggesting that dKeap1 is required for heterochromatin formation and/or maintenance (Carlson et al ., 2019). Given that dKeap1 overexpression relocated Lamin, we tested whether ectopic dKeap1 can alter the organization of heterochromatin in the nucleus.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies found that knockout of dKeap1 reduced the level of heterochromatin marker histone H3K9me2, suggesting that dKeap1 is required for heterochromatin formation and/or maintenance (Carlson et al ., 2019). Given that dKeap1 overexpression relocated Lamin, we tested whether ectopic dKeap1 can alter the organization of heterochromatin in the nucleus.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the well-established model in which Keap1 and Nrf2 factors control antioxidant and detoxifying transcription, the mechanisms whereby Keap1 and Nrf2 regulate developmental genes remains unclear. Keap1 and Nrf2 likely function both in gene activation as transcription activators and in gene silencing by regulating heterochromatin (Carlson et al ., 2022; Carlson et al ., 2019; Deng & Kerppola, 2013, 2014). We hypothesize that Keap1-Nrf2 conducts different roles by forming complexes with different protein partners.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Silencing mediator for retinoid and thyroid hormone receptor (SMRT), a transcriptional repressor that mediates histone deacetylation, can interact with Nrf2 Neh4/5 domains and inhibit Nrf2-induced GSTA2 expression [81]. Notably, a recent study in Drosophila showed that depletion of CncC or dKeap1 suppresses pericentric silencing and decreases the level of heterochromatin marker H3K9me2, providing direct evidence in support of the epigenetic role of Keap1/Nrf2 family proteins in chromatin remodeling [82].…”
Section: Epigenetic Machinerymentioning
confidence: 92%